2005
DOI: 10.1080/13651500510014729
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone in the treatment of behavioural and psychological symptoms of dementia in patients diagnosed with vascular or mixed-type dementia

Abstract: Objective Studies have found that the atypical antipsychotic drug, risperidone, reduces non-cognitive symptoms, such as aggression, agitation, and psychosis, in patients with Alzheimer's disease. This study assessed whether these effects extend to patients with vascular or mixed-type dementia. Methods In this multicentre, open-label, prospective study, 75 elderly patients with vascular or mixed-type dementia and concomitant behavioural and psychological symptoms were treated with risperidone for up to 6 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Alfonso et al [57] showed that risperidone was an effective treatment for both VaD and MixD sub-types and it is, up to date, the sole direct comparison between specific antipsychotic prescribing patterns in different dementia sub-types. The use of risperidone at a mean dose of 1.6 mg/day for 6 months was of clinical benefit in the treatment of aggression, psychomotor agitation and psychosis.…”
Section: Antipsychotic Use Across Dementia Sub-types (Vad Ad Versmentioning
confidence: 99%
“…Alfonso et al [57] showed that risperidone was an effective treatment for both VaD and MixD sub-types and it is, up to date, the sole direct comparison between specific antipsychotic prescribing patterns in different dementia sub-types. The use of risperidone at a mean dose of 1.6 mg/day for 6 months was of clinical benefit in the treatment of aggression, psychomotor agitation and psychosis.…”
Section: Antipsychotic Use Across Dementia Sub-types (Vad Ad Versmentioning
confidence: 99%
“…Cruz-Jentoft et al 11 conducted a multicenter, open-label, prospective study treating 75 patients with vascular or mixed-type dementia and concomitant behavioral and psychological symptoms with risperidone for up to 6 months. Risperidone decreased the frequency and severity of overall behavioral and psychological symptoms.…”
Section: Risperidonementioning
confidence: 99%
“…Cruz-Jentoft et al, reported two cases of hypotension, one somnolence, and one paresthesia[39]. In the Mintzer et al, study, patients who were given risperidone experienced a higher incidence of treatment-related side effects compared to those given a placebo, with somnolence being reported signi cantly more often in the risperidone group (16.2% versus 4.6%)[42].…”
mentioning
confidence: 95%
“…Seven studies found no signi cant changes in the scores of the adverse event paired with the beginning of the study in the risperidone group[17-19, 31, 36-38]. In the Cruz-Jentoft et al, study, the Undersøgelser Side Effects Rating Scale for Clinicians (UKU-SERS-Clin) extrapyramidal subscale ratings indicating a temporary reduction in extrapyramidal symptoms during the course of the study, with signi cantly lower score at month 3[39]. On the other hand, De Deyn et al found that the frequency of combined EPS-related adverse effects was higher in the complete risperidone group, with a rate of 16.3%, compared to the placebo group's rate of 11.6%, and this seemed to vary with the dose[40].…”
mentioning
confidence: 99%